High-barrier polyvinyl alcohol biaxially oriented film and preparation method thereof
By using porous polyimide microspheres and modified polytetrafluoroethylene fibers in high barrier coatings to form a cross-passing network, the problem of interface bond stability caused by insufficient thermal stability of polyvinyl alcohol is solved, and the application stability of high barrier polyvinyl alcohol bidirectional tensile film is significantly improved.
Patent Information
- Application Number
- CN202510095391.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
Polyvinyl alcohol has poor thermal stability, resulting in loss of interface bonding stability between the high barrier coating and the polyvinyl alcohol bidirectional stretch film substrate, thereby affecting the high barrier performance.
Porous polyimide microspheres and modified polytetrafluoroethylene fibers are used to form a cross-passing network in the high-barrier coating to improve the thermal stability and interface bonding stability of the coating.
The interface bond stability between the high-barrier coating and the polyvinyl alcohol bidirectional stretch film substrate is significantly improved under the temperature change environment, and the application stability of the high-barrier polyvinyl alcohol bidirectional stretch film is extended.
Smart Images

Figure BDA0005252721360000101 
Figure BDA0005252721360000111 
Figure BDA0005252721360000151
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of high barrier films, and more specifically, to a high barrier polyvinyl alcohol biaxially stretched film and a preparation method thereof. Background Art
[0002] Polyvinyl alcohol film is a film material with polyvinyl alcohol as the main component. It has excellent water solubility, water resistance, transparency and glossiness. Because of its gas barrier, moisture-proof, waterproof and oil-proof properties, it is widely used in food packaging, pharmaceutical packaging, electronic packaging and other fields.
[0003] The polyvinyl alcohol biaxially oriented film is made by biaxially stretching first longitudinally and then transversely. It has the advantages of fast forming speed, high production efficiency, and better mechanical strength and thickness uniformity of the obtained film.
[0004] Furthermore, the high-barrier polyvinyl alcohol biaxially oriented film is obtained by single-sided coating of a polyvinyl alcohol biaxially oriented film substrate to form a high-barrier coating. This film has excellent barrier properties and can extend the shelf life of the packaged contents. It is particularly suitable for the packaging of high-end foods containing oils and fats, and has the dual effects of barrier and preservation.
[0005] For example, the invention patent with authorization number CN118288653B discloses a high-barrier polyvinyl alcohol biaxially stretched film and a preparation method thereof, a high-barrier polyvinyl alcohol biaxially stretched film, the high-barrier polyvinyl alcohol biaxially stretched film is obtained by coating a high-barrier polyvinyl alcohol coating on a multilayer polyethylene substrate film and curing it, the high-barrier polyvinyl alcohol coating comprises the following components: chitosan modified polyurethane, polyvinyl alcohol, glutaraldehyde, EDC, modified filler and deionized water.
[0006] Regarding the above-mentioned related technologies, the inventors believe that polyvinyl alcohol has poor thermal stability and is prone to uneven shrinkage deformation when subjected to drastic temperature changes, which will lead to a loss of interfacial bonding stability between the high-barrier coating and the polyvinyl alcohol biaxially stretched film substrate, and the overall barrier properties of the high-barrier polyvinyl alcohol biaxially stretched film will also be lost.
[0007] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention
[0008] In order to improve the interfacial bonding stability between a high-barrier coating and a polyvinyl alcohol biaxially oriented film substrate under a temperature-changing environment, the present application provides a high-barrier polyvinyl alcohol biaxially oriented film and a preparation method thereof.
[0009] In the first aspect, the present application provides a high barrier polyvinyl alcohol biaxially oriented film, which adopts the following technical solution:
[0010] A high-barrier polyvinyl alcohol biaxially oriented film comprises a polyvinyl alcohol biaxially oriented film substrate and a high-barrier coating formed by single-sided coating on the polyvinyl alcohol biaxially oriented film substrate, wherein the high-barrier coating is made of the following raw materials in parts by weight:
[0011] Polyvinyl alcohol 5-7 parts;
[0012] Amino resin 0.5-1 part;
[0013] Catalyst 0.01-0.3 parts;
[0014] 90-95 parts of deionized water;
[0015] Filler 0.01-0.05 parts;
[0016] Add 0.01-0.1 parts of additives;
[0017] Polytetrafluoroethylene fiber 0.01-0.03 parts;
[0018] Porous polyimide microspheres 0.04-0.08 parts;
[0019] The porous polyimide microspheres are prepared by the following steps:
[0020] S1, dissolving 4,4'-diaminodiphenyl ether in a DMF solution to obtain a dispersed phase; mixing a surfactant with liquid paraffin to form a continuous phase; then mixing and stirring the dispersed phase and the continuous phase, and obtaining a mixed solution after ultrasonic emulsification;
[0021] S2, adding a porogen to the mixed solution obtained in step S1, adding polyoxymethylenedimethyl ether during stirring, adding a mixed solution of pyridine and acetic anhydride after the reaction is completed to carry out imidization, then obtaining a semi-finished product after solidification, centrifugation, precipitation, washing and drying, and finally performing a gradient temperature increase heat treatment to obtain porous polyimide microspheres.
[0022] By adopting the above technical scheme, in the preparation of porous microspheres, the mixed liquid formed by the dispersed phase and the continuous phase provides a microreactor for the polymerization reaction, and then the polymerization reaction is brought about by the use of porogens and polyoxymethylenedimethyl ether, followed by the addition of a mixed liquid of pyridine and acetic anhydride for imidization, and the porogen is volatilized and escaped by heat release during the imidization reaction, thereby completing the sphering and pore formation, and finally performing a temperature-raising heat treatment, which further ensures the stability of the formed pores, and obtains porous polyimide microspheres with good microporous structure and spherical morphology. The use of porous polyimide microspheres as raw materials in the preparation of high-barrier coatings can improve the stability of the overall structure of the high-barrier coating by utilizing the thermal stability of the porous polyimide microspheres themselves and the pore adsorption characteristics. At the same time, polytetrafluoroethylene fibers have excellent thermal stability, and can form a three-dimensional interactive structural system in the high-barrier coating, thereby improving the thermal stability of the high-barrier coating. When polytetrafluoroethylene fibers and porous polyimide microspheres are used together, the two can have an excellent compounding and synergistic effect on each other, and can form a cross-penetration network of polytetrafluoroethylene fibers with porous polyimide microspheres as connecting nodes in the high-barrier coating, which can significantly improve the interfacial bonding stability between the high-barrier coating and the polyvinyl alcohol biaxially stretched film substrate in a temperature-changing environment, thereby obtaining a high-barrier polyvinyl alcohol biaxially stretched film with better application quality.
[0023] Preferably, the polytetrafluoroethylene fiber is modified before use, and the specific operation is as follows:
[0024] The polytetrafluoroethylene fiber raw material is treated with sodium naphthalene tetrahydrofuran etching solution, then immersed in isopropanol solution, then immersed in sodium dodecyl sulfate solution, and finally vacuum dried to obtain modified polytetrafluoroethylene fiber.
[0025] By adopting the above technical scheme, in the modification treatment of polytetrafluoroethylene fiber, sodium naphthalene tetrahydrofuran etching solution is first used for treatment, which will tear off some fluorine atoms on the surface of the polytetrafluoroethylene fiber and leave a carbonized layer and polar groups on the surface of the polytetrafluoroethylene fiber; then it is immersed in isopropyl alcohol solution and sodium dodecyl sulfate solution in turn, which can graft hydrophilic groups on the surface of the polytetrafluoroethylene fiber; the modified polytetrafluoroethylene fiber obtained at this time can be more evenly dispersed in the raw material mixing system of the high barrier coating, and form a closer bond with the porous polyimide microspheres, and can also play a more prominent compounding and synergistic role with each other, so that the interface bonding stability between the high barrier coating and the polyvinyl alcohol biaxially stretched film substrate in a temperature change environment is better.
[0026] Preferably, the diameter of the polytetrafluoroethylene fiber is 100-200 nm; the particle size of the porous polyimide microsphere is 16-40 μm, and the pore size is 200-500 nm.
[0027] By adopting the above technical scheme, when the polytetrafluoroethylene fibers and porous polyimide microspheres of the above specifications are matched, the cross-penetration network of polytetrafluoroethylene fibers with porous polyimide microspheres as connecting nodes is formed to be relatively uniform as a whole, and can exert a relatively stable effect at the interface between the high-barrier coating and the polyvinyl alcohol biaxially stretched film substrate, thereby making the application stability of the high-barrier polyvinyl alcohol biaxially stretched film better in a temperature-changing environment.
[0028] Preferably, the weight ratio of the polytetrafluoroethylene fiber to the porous polyimide microspheres is 2:5.
[0029] By adopting the above technical scheme, when the polytetrafluoroethylene fibers and porous polyimide microspheres in the above weight ratio are used in combination, the two can form a relatively uniform and comprehensive combination, and the effect of their mutual cooperation is relatively excellent and stable, and finally a high-barrier polyvinyl alcohol biaxially stretched film with better application quality in a temperature-changing environment can be obtained.
[0030] Preferably, the filler is one or a combination of bentonite, calcium carbonate, mica powder, silica powder, talc and barium sulfate.
[0031] By adopting the above technical solution, the filler can increase the viscosity of the coating, make the coating more stable during construction, reduce fluidity and dripping, improve the adhesion and covering power of the coating, and also bring about corresponding performance improvements according to the characteristics of the filler. The above fillers are all suitable for the preparation of high barrier coatings and can be selected and combined according to actual needs.
[0032] Preferably, the additive is one or a combination of defoaming agent, dispersant, plasticizer, antioxidant and preservative.
[0033] By adopting the above technical scheme, the above types of additives are all suitable for the preparation of high barrier coatings, and can stably play their own roles in the high barrier coatings, improve the bonding between the raw materials of each component and the coating performance, and can be selected and combined according to actual needs.
[0034] Preferably, 0.01-0.03 parts by weight of a functional additive is added to the raw materials for preparing the high barrier coating, and the functional additive is composed of titanium oxide nanotubes and a rare earth mixture, and the weight ratio of the titanium oxide nanotubes to the rare earth mixture is (10-18):1.
[0035] By adopting the above technical scheme, titanium oxide nanotubes have excellent thermal stability and temperature resistance. When used in high barrier coatings, they can improve the application stability of the high barrier coatings in temperature-changing environments; the rare earth mixture can significantly improve the temperature-changing resistance of the high barrier coatings through its unique physical and chemical properties; and when titanium oxide nanotubes and rare earth mixtures are used as functional additives, the two can exert an excellent compounding effect on each other. By loading titanium oxide nanotubes with rare earth mixtures, on the one hand, the cross-penetration network structure of polytetrafluoroethylene fibers with porous polyimide microspheres as connecting nodes can be enriched and strengthened, and on the other hand, the above network structure can be caused to act on the interface between the high barrier coating and the polyvinyl alcohol biaxially stretched film substrate, and exert an excellent stress conduction effect in a temperature-changing environment, thereby significantly improving the application stability of the high barrier polyvinyl alcohol biaxially stretched film in a temperature-changing environment.
[0036] Preferably, the rare earth mixture consists of yttrium oxide and cerium oxide in a weight ratio of (0.8-1.2):1.
[0037] By adopting the above technical scheme, yttrium oxide can significantly improve the temperature change resistance of the coating, and can enhance the adhesion of the coating, so that it can better adhere to the substrate; the crystal structure of cerium oxide can remain stable under temperature changes, and is not easy to deform or crack, which can improve the temperature change resistance of the coating; and when yttrium oxide and cerium oxide are used to form a rare earth mixture according to the above weight ratio, the treatment can not only play the above-mentioned role, but also can play a relatively excellent and stable compound synergistic effect with titanium oxide nanotubes, so that the high barrier polyvinyl alcohol biaxially stretched film has better application stability under temperature change environment.
[0038] Preferably, the weight ratio of the titanium oxide nanotubes to the rare earth mixture is 15:1.
[0039] By adopting the above technical scheme, when the titanium oxide nanotubes and rare earth mixtures in the above weight ratio are used in combination, the synergistic effect brought by each other is more significant, so that the corresponding effect brought by the application of functional additives is better, and the high barrier coating and the polyvinyl alcohol biaxially stretched film substrate can maintain relatively excellent bonding stability under temperature change environment.
[0040] In a second aspect, the present application provides a method for preparing a high-barrier polyvinyl alcohol biaxially stretched film, using the following technical solution:
[0041] A method for preparing a high-barrier polyvinyl alcohol biaxially stretched film comprises the following steps:
[0042] (1) preparing raw materials including polyvinyl alcohol, amino resin, catalyst, deionized water, filler, additive, polytetrafluoroethylene fiber and porous polyimide microspheres according to a ratio;
[0043] (2) after mixing the polyvinyl alcohol and deionized water in step (1), adding fillers, additives, polytetrafluoroethylene fibers and porous polyimide microspheres during heating and stirring, then cooling, adding amino resin and catalyst, stirring and filtering, and obtaining a high barrier coating;
[0044] (3) The high barrier coating in step (2) is coated on one side of the polyvinyl alcohol biaxially stretched film substrate to form a high barrier coating after molding, thereby finally obtaining a high barrier polyvinyl alcohol biaxially stretched film.
[0045] By adopting the above technical scheme, the above method is simple to operate, the raw materials in the high-barrier coating can be fully coordinated and exert excellent effects, thereby obtaining a high-barrier coating of excellent quality, and when the high-barrier coating is coated on one side of the polyvinyl alcohol biaxially stretched film substrate, the overall operation is also relatively convenient, and the whole is also suitable for large-scale industrial production.
[0046] In summary, this application has the following beneficial effects:
[0047] 1. The present application uses polytetrafluoroethylene fibers and porous polyimide microspheres in the high-barrier coating, and through the compounding of the two, a polytetrafluoroethylene fiber cross-penetration network with porous polyimide microspheres as connecting nodes can be formed in the high-barrier coating, which can significantly improve the interface bonding stability between the high-barrier coating and the polyvinyl alcohol biaxially stretched film substrate under a temperature change environment, thereby obtaining a high-barrier polyvinyl alcohol biaxially stretched film with better application quality;
[0048] 2. The present application uses a functional additive composed of titanium oxide nanotubes and a rare earth mixture in the high-barrier coating. On the one hand, it can enrich and strengthen the cross-penetration network structure of polytetrafluoroethylene fibers with porous polyimide microspheres as connecting nodes. On the other hand, it can promote the above-mentioned network structure to act on the interface between the high-barrier coating and the polyvinyl alcohol biaxially stretched film substrate, and exert an excellent stress conduction effect under a temperature-changing environment, thereby significantly improving the application stability of the high-barrier polyvinyl alcohol biaxially stretched film under a temperature-changing environment. DETAILED DESCRIPTION
[0049] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0050] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available:
[0051] The polyvinyl alcohol biaxially oriented film substrate was purchased from Shenzhen Fujinfang Film Co., Ltd., with a thickness of 0.075 mm;
[0052] Polyvinyl alcohol 26-99L was purchased from Guangxi Wanwei Biomass Technology Co., Ltd.;
[0053] Amino resin was purchased from Jinan Huate Chemical Co., Ltd. CYMEL325;
[0054] Polytetrafluoroethylene fiber was purchased from Xiamen Borun Fluoride Material Technology Co., Ltd. PTFE short fiber;
[0055] Titanium oxide nanotubes were purchased from Beijing Dekedaojin Technology Co., Ltd., model DK-TiO2-00102.
[0056] Preparation examples of raw materials and / or intermediates
[0057] Preparation Example 1
[0058] A porous polyimide microsphere is prepared by the following steps:
[0059] S1. Dissolve 4,4'-diaminodiphenyl ether in DMF solution until saturated to obtain a dispersed phase; mix a surfactant and liquid paraffin at a weight ratio of 1:9 to form a continuous phase; then mix the dispersed phase and the continuous phase at a volume ratio of 1:4 and stir, and ultrasonically emulsify for 2 hours to obtain a mixed solution;
[0060] S2. Add 50% volume of porogen to the mixed solution obtained in step S1, add polyoxymethylenedimethyl ether in an amount equal to that of the mixed solution during stirring, add 5% weight of a mixed solution of pyridine and acetic anhydride after the reaction is completed for 6 hours for imidization, wherein the molar ratio of pyridine to acetic anhydride is 1:1, and then obtain a semi-finished product after solidification, centrifugation, precipitation, washing and drying, and finally perform gradient temperature rise heat treatment at a heating rate of 10°C / min, and stay at 100°C, 200°C, 300°C and 350°C for 1 hour respectively, and finally cool to obtain porous polyimide microspheres.
[0061] Note: The surfactant used in the above operation is Tween 80 and the porogen is methanol; the particle size of the porous polyimide microspheres is 28 μm and the pore size is 350 nm.
[0062] Preparation Example 2
[0063] A porous polyimide microsphere, which is different from the preparation example 1 in that the porous polyimide microsphere has a particle size of 16 μm and a pore size of 200 nm.
[0064] Preparation Example 3
[0065] A porous polyimide microsphere, which is different from the preparation example 1 in that the porous polyimide microsphere has a particle size of 40 μm and a pore size of 500 nm.
[0066] Preparation Example 4
[0067] A modified polytetrafluoroethylene fiber is prepared by the following steps:
[0068] The polytetrafluoroethylene fiber raw material was treated with 5% sodium naphthalene tetrahydrofuran etching solution for 10 minutes, then immersed in isopropanol solution for 30 minutes, then immersed in 20% sodium dodecyl sulfate solution for 7 hours, and finally vacuum dried to obtain modified polytetrafluoroethylene fiber.
[0069] Note: In the above operation, the diameter of the polytetrafluoroethylene fiber is 150nm.
[0070] Preparation Example 5
[0071] A modified polytetrafluoroethylene fiber, which is different from the preparation example 4 in that the diameter of the polytetrafluoroethylene fiber is 100 nm.
[0072] Preparation Example 6
[0073] A modified polytetrafluoroethylene fiber, which is different from Preparation Example 4 in that the diameter of the polytetrafluoroethylene fiber is 200 nm.
[0074] Example
[0075] Example 1
[0076] A high-barrier polyvinyl alcohol biaxially stretched film comprises a polyvinyl alcohol biaxially stretched film substrate and a high-barrier coating formed by single-sided coating on the polyvinyl alcohol biaxially stretched film substrate. The raw materials for preparing the high-barrier coating and their corresponding weights are shown in Table 1. The high-barrier polyvinyl alcohol biaxially stretched film is prepared by the following steps:
[0077] (1) preparing raw materials including polyvinyl alcohol, amino resin, catalyst, deionized water, filler, additive, polytetrafluoroethylene fiber and porous polyimide microspheres according to a ratio;
[0078] (2) after mixing the polyvinyl alcohol and deionized water in step (1), adding fillers, additives, polytetrafluoroethylene fibers and porous polyimide microspheres during heating and stirring, then cooling, adding amino resin and catalyst, stirring and filtering, and obtaining a high barrier coating;
[0079] (3) The high barrier coating in step (2) is coated on one side of the polyvinyl alcohol biaxially stretched film substrate to form a high barrier coating after molding, thereby finally obtaining a high barrier polyvinyl alcohol biaxially stretched film.
[0080] Note: In the above operation, the thickness of the high barrier coating is 0.25 μm; the porous polyimide microspheres are obtained in Preparation Example 1; the filler is bentonite; the catalyst is citric acid; the additive is a composition of a defoamer and a dispersant in a weight ratio of 2:1, wherein the defoamer is Evonik Tego Foamex 810, and the dispersant is San Nopco polycarboxylate sodium salt SN-DISPERSANT 5040.
[0081] Example 2-3
[0082] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that the raw materials for preparing the high barrier coating and their corresponding weights are shown in Table 1.
[0083] Table 1 Raw materials for preparing high barrier coatings in Examples 1-3 and their weight portions (kg / portion)
[0084]
[0085]
[0086] Example 4
[0087] A high barrier polyvinyl alcohol biaxially stretched film is different from Example 1 in that the total amount of tetrafluoroethylene fiber and porous polyimide microspheres remains unchanged, and the weight ratio of the two is adjusted to 2:5.
[0088] Example 5
[0089] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that the porous polyimide microspheres are obtained in Preparation Example 2.
[0090] Example 6
[0091] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that the porous polyimide microspheres are obtained in Preparation Example 3.
[0092] Example 7
[0093] A high barrier polyvinyl alcohol biaxially oriented film, which is different from Example 1 in that the polytetrafluoroethylene fiber is modified before use, and the modified polytetrafluoroethylene fiber is obtained from Preparation Example 4.
[0094] Example 8
[0095] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that the polytetrafluoroethylene fiber is modified before use, and the modified polytetrafluoroethylene fiber is obtained from Preparation Example 5.
[0096] Example 9
[0097] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that the polytetrafluoroethylene fiber is modified before use, and the modified polytetrafluoroethylene fiber is obtained from Preparation Example 6.
[0098] Example 10
[0099] A high-barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that 0.02 parts by weight of a functional additive is further added to the raw materials for preparing the high-barrier coating, the functional additive is composed of titanium oxide nanotubes and a rare earth mixture in a weight ratio of 15:1, and the functional additive is added together with polytetrafluoroethylene fibers and porous polyimide microspheres;
[0100] Meanwhile, the rare earth mixture is composed of yttrium oxide and cerium oxide in a weight ratio of 1:1.
[0101] Embodiment 11
[0102] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that the weight portion of the functional additive added is 0.01 parts.
[0103] Example 12
[0104] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that the weight portion of the functional additive added is 0.03 parts.
[0105] Example 13
[0106] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that the functional additive is composed of titanium oxide nanotubes and a rare earth mixture in a weight ratio of 14:1.
[0107] Embodiment 14
[0108] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that the functional additive is composed of titanium oxide nanotubes and a rare earth mixture in a weight ratio of 10:1.
[0109] Embodiment 15
[0110] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that the functional additive is composed of titanium oxide nanotubes and a rare earth mixture in a weight ratio of 18:1.
[0111] Example 16
[0112] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that the rare earth mixture consists of yttrium oxide and cerium oxide in a weight ratio of 0.8:1.
[0113] Embodiment 17
[0114] A high barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that the rare earth mixture consists of yttrium oxide and cerium oxide in a weight ratio of 1.2:1.
[0115] Embodiment 18
[0116] A high-barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that titanium oxide nanotubes are not used in the raw materials for preparing the high-barrier coating.
[0117] Embodiment 19
[0118] A high-barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that no rare earth mixture is used in the raw materials for preparing the high-barrier coating.
[0119] Comparative Example
[0120] Comparative Example 1
[0121] A high-barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that polytetrafluoroethylene fiber is not used in the raw materials for preparing the high-barrier coating.
[0122] Comparative Example 2
[0123] A high-barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that porous polyimide microspheres are not used in the raw materials for preparing the high-barrier coating.
[0124] Comparative Example 3
[0125] A high-barrier polyvinyl alcohol biaxially stretched film, which is different from Example 1 in that polytetrafluoroethylene fibers and porous polyimide microspheres are not used in the raw materials for preparing the high-barrier coating.
[0126] Comparative Example 4
[0127] A high-barrier polyvinyl alcohol biaxially stretched film, which is different from Example 10 in that polytetrafluoroethylene fibers and porous polyimide microspheres are not used in the raw materials for preparing the high-barrier coating.
[0128] Performance testing
[0129] Test samples: The high barrier polyvinyl alcohol biaxially oriented film obtained in Example 1-19 was used as test sample 1-19, and the high barrier polyvinyl alcohol biaxially oriented film obtained in Comparative Example 1-4 was used as control sample 1-4.
[0130] Test method: (1) Peel strength test: the peel strength test of the high barrier coating on the high barrier polyvinyl alcohol biaxially stretched film is carried out using a peel tester. The principle of the peel tester is to fix the film to be tested using the suction cup or clamp on the tester, and then separate it from the substrate at a certain speed and force, record the peel force and peel speed, and then calculate the peel strength. The peel test instrument is the HTS-BLY2510 fully computer-controlled peel strength tester produced by Nakano Seiko.
[0131] (2) Oxygen barrier performance test: According to GB / T1038-2000, the oxygen barrier performance of the membrane was tested using an air permeability tester. The sample membrane was cut into a circle with a diameter of 8.5 cm using a standard sample knife. Three samples of each sample were measured and the average value was taken to obtain the oxygen permeability coefficient (1×10 -15 cm 3 cm / cm 2 ·s·Pa).
[0132] (3) Water vapor barrier performance test: According to GB / T 1037-88 "Test method for water vapor permeability of plastic film and sheet", the film was cut into a circle with an area of 50 cm2 and tested using a water vapor transmission rate tester to obtain the water vapor transmission rate g / (m 2 ·24h).
[0133] After taking the high-barrier polyvinyl alcohol biaxially stretched film for the above test, the value obtained is recorded as the initial value; then the high-barrier polyvinyl alcohol biaxially stretched film is placed in a high and low temperature alternating test box, the initial temperature is 25°C, first the temperature is increased to 85°C at 3°C / min, then the temperature is reduced to -20°C at 1.5°C / min, and then the temperature is increased to 25°C at 2°C / min, which is recorded as 1 cycle. After 15 cycles, the above test is performed in the same way, and the value obtained is recorded as the experimental value; then the peel strength loss rate, oxygen barrier performance loss rate and water vapor barrier performance loss rate are calculated, and they are calculated by "(initial value-experimental value) / initial value".
[0134] After completing the above tests on test samples 1-19 and control samples 1-4 in sequence, the corresponding results are recorded in Table 2.
[0135] Table 2 Test results of test samples 1-19 and control samples 1-4
[0136]
[0137]
[0138] Combining Example 1 and Comparative Examples 1-3 and Table 2, it can be seen that the use of polytetrafluoroethylene fibers and porous polyimide microspheres in the high barrier coating can significantly improve the interfacial bonding stability between the high barrier coating and the polyvinyl alcohol biaxially stretched film substrate under a temperature change environment, and the peel strength loss rate, oxygen barrier performance loss rate and water vapor barrier performance loss rate of the high barrier polyvinyl alcohol biaxially stretched film obtained by the above test are significantly reduced, indicating that the application stability of the high barrier polyvinyl alcohol biaxially stretched film is excellent. At the same time, if polytetrafluoroethylene fibers or porous polyimide microspheres are used alone in the high barrier coating, although it can bring about the improvement of the corresponding performance, the improvement effect is limited, and the sum of the improvement effects brought by the use of each of the two alone is far less than the excellent effect brought by the compounding of the two. It can be seen that there is a compounding synergistic effect between polytetrafluoroethylene fibers and porous polyimide microspheres. Combining Examples 2-4 and Table 2, it can be seen that when the weight ratio of polytetrafluoroethylene fiber to porous polyimide microspheres is 2:5, a high-barrier polyvinyl alcohol biaxially oriented film with better application quality under temperature-changing environments can be finally obtained.
[0139] It can be seen from Example 1 and Examples 10-15 and Table 2 that the use of a functional additive composed of titanium oxide nanotubes and a rare earth mixture in a high barrier coating can further reduce the peel strength loss rate, oxygen barrier performance loss rate and water vapor barrier performance loss rate obtained in the test, indicating that the application stability of the high barrier polyvinyl alcohol biaxially stretched film in a temperature change environment is further improved; wherein, when the weight ratio of titanium oxide nanotubes to the rare earth mixture is 15:1, the corresponding effect brought about by the application of the functional additive is better. It can be seen from Examples 16-17 and Table 2 that the rare earth mixture is composed of yttrium oxide and cerium oxide in a weight ratio of (0.8-1.2):1, and can play a relatively excellent and stable coordination role with titanium oxide nanotubes. Combined with Examples 18-19 and Table 2, it can be seen that if titanium oxide nanotubes or rare earth mixtures are used alone, the improvement effect brought is limited, and the sum of the improvement effects brought by the two are far less than the excellent effect brought by the combination of the two. It can be seen that the combination of titanium oxide nanotubes and rare earth mixtures can bring a significant improvement effect of 1+1>2.
[0140] It can be seen from Example 1, Example 10 and Comparative Examples 3-4 and Table 2 that if the high-barrier coating lacks the use of polytetrafluoroethylene fibers and porous polyimide microspheres, the corresponding effects brought by the functional additives will be greatly reduced, indicating that the functional additives can significantly strengthen the cross-penetration network structure of polytetrafluoroethylene fibers with porous polyimide microspheres as connecting nodes, thereby significantly improving the application stability of the high-barrier polyvinyl alcohol biaxially stretched film under temperature variation.
[0141] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high barrier polyvinyl alcohol biaxially oriented film, characterized in that: The invention comprises a polyvinyl alcohol biaxially oriented film substrate and a high barrier coating formed by single-sided coating on the polyvinyl alcohol biaxially oriented film substrate, wherein the high barrier coating is made of the following raw materials in parts by weight: Polyvinyl alcohol 5-7 parts; Amino resin 0.5-1 part; Catalyst 0.01-0.3 parts; 90-95 parts of deionized water; Filler 0.01-0.05 parts; Add 0.01-0.1 parts of additives; Polytetrafluoroethylene fiber 0.01-0.03 parts; Porous polyimide microspheres 0.04-0.08 parts; The porous polyimide microspheres are prepared by the following steps: S1, dissolving 4,4'-diaminodiphenyl ether in a DMF solution to obtain a dispersed phase; mixing a surfactant with liquid paraffin to form a continuous phase; then mixing and stirring the dispersed phase and the continuous phase, and obtaining a mixed solution after ultrasonic emulsification; S2, adding a porogen to the mixed solution obtained in step S1, adding polyoxymethylenedimethyl ether during stirring, adding a mixed solution of pyridine and acetic anhydride after the reaction is completed to carry out imidization, then obtaining a semi-finished product after solidification, centrifugation, precipitation, washing and drying, and finally performing a gradient temperature increase heat treatment to obtain porous polyimide microspheres.
2. The high barrier polyvinyl alcohol biaxially oriented film according to claim 1, characterized in that: The polytetrafluoroethylene fiber is modified before application, and the specific operation is as follows: The polytetrafluoroethylene fiber raw material is treated with sodium naphthalene tetrahydrofuran etching solution, then immersed in isopropanol solution, then immersed in sodium dodecyl sulfate solution, and finally vacuum dried to obtain modified polytetrafluoroethylene fiber.
3. The high barrier polyvinyl alcohol biaxially oriented film according to claim 1, characterized in that: The diameter of the polytetrafluoroethylene fiber is 100-200nm; the particle size of the porous polyimide microsphere is 16-40μm, and the pore size is 200-500nm.
4. The high barrier polyvinyl alcohol biaxially oriented film according to claim 1, characterized in that: The weight ratio of the polytetrafluoroethylene fiber to the porous polyimide microspheres is 2:
5.
5. The high barrier polyvinyl alcohol biaxially oriented film according to claim 1, characterized in that: The filler is one or a combination of bentonite, calcium carbonate, mica powder, silica powder, talc powder and barium sulfate.
6. The high barrier polyvinyl alcohol biaxially oriented film according to claim 1, characterized in that: The additive is one or a combination of defoaming agent, dispersant, plasticizer, antioxidant and preservative.
7. The high barrier polyvinyl alcohol biaxially oriented film according to claim 1, characterized in that: The raw materials for preparing the high barrier coating are also added with 0.01-0.03 parts by weight of a functional additive, which is composed of titanium oxide nanotubes and a rare earth mixture, and the weight ratio of the titanium oxide nanotubes to the rare earth mixture is (10-18):
1.
8. The high barrier polyvinyl alcohol biaxially oriented film according to claim 7, characterized in that: The rare earth mixture is composed of yttrium oxide and cerium oxide in a weight ratio of (0.8-1.2):
1.
9. The high barrier polyvinyl alcohol biaxially oriented film according to claim 7, characterized in that: The weight ratio of the titanium oxide nanotubes to the rare earth mixture is 15:
1.
10. The method for preparing the high barrier polyvinyl alcohol biaxially oriented film according to claim 1, characterized in that: The following steps are involved: (1) preparing raw materials including polyvinyl alcohol, amino resin, catalyst, deionized water, filler, additive, polytetrafluoroethylene fiber and porous polyimide microspheres according to a ratio; (2) after mixing the polyvinyl alcohol and deionized water in step (1), adding fillers, additives, polytetrafluoroethylene fibers and porous polyimide microspheres during heating and stirring, then cooling, adding amino resin and catalyst, stirring and filtering, and obtaining a high barrier coating; (3) The high barrier coating in step (2) is coated on one side of the polyvinyl alcohol biaxially stretched film substrate to form a high barrier coating after molding, thereby finally obtaining a high barrier polyvinyl alcohol biaxially stretched film.
Citation Information
Patent Citations
A high-barrier polyvinyl alcohol biaxially stretched film and preparation method thereof
CN118288653B
Cited By
Transparent biomass polyvinyl alcohol hydrogel as well as preparation method and application thereof
CN120365592A
A transparent biomass polyvinyl alcohol hydrogel and its preparation method and application
CN120365592B